As an educational tool the importance of informal studies/studios in architectural design education; case of Walking Istanbul 1&2 - Polatoglu, Cigdem; Vural, S. Mujdem (ELSEVIER SCIENCE BV, 2012)
Design education is the most important part of architectural education. Formal architectural education (training), followed by an architect in the candidate's training period, is a whole consisting of theoretical and practical courses. In spite of this programme package, in design education, student acquires to experience the design by his/her own and this is the only way to learn how to design. In this context, aside from formal architectural education informal studies such as workshops, seminars, conferences, exhibitions, competitions, excavation, etc. have an undeniable importance. In design education, Informal Studies have some outstanding results on developing design thinking skills, learning by doing, creating motivation, intuitive knowledge and self-confidence and at the same time these studies are a suitable tool for the LLP- lifelong learning programme. In this paper, as an informal study example two workshops will be discussed to evaluate the contributions of such informal studies on student's individual and collective learning styles, design thinking techniques and practices. (C) 2012 Published by Elsevier Ltd.
Keywords: Design education in architecture; informal studios; observation and freehand drawings; Education & Educational Research